2014
DOI: 10.5966/sctm.2014-0035
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Analysis of DNA Methylation in CD34+ Hematopoietic Progenitors in Myelodysplastic Syndrome

Abstract: Myelodysplastic syndrome (MDS) is a disorder of hematopoietic stem cells (HSCs) that is often treated with DNA methyltransferase 1 (DNMT1) inhibitors (5-azacytidine [AZA], 5-aza-29-deoxycytidine), suggesting a role for DNA methylation in disease progression. How DNMT inhibition retards disease progression and how DNA methylation contributes to MDS remain unclear. We analyzed global DNA methylation in purified CD34+ hematopoietic progenitors from MDS patients undergoing multiple rounds of AZA treatment. Differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…In addition, it is important to note that our analyses did not detect the emergence of acquired genetic and/or cytogenetic abnormalities when sPAP was identified. Based on the findings of a previous study describing changes in the clonal composition under azacitidine (29)(30)(31), the disease progression of our case may also have been due to clonal changes. Further studies are warranted in order to clarify the pathogenesis of the development of MDS/sPAP.…”
Section: Discussionsupporting
confidence: 69%
“…In addition, it is important to note that our analyses did not detect the emergence of acquired genetic and/or cytogenetic abnormalities when sPAP was identified. Based on the findings of a previous study describing changes in the clonal composition under azacitidine (29)(30)(31), the disease progression of our case may also have been due to clonal changes. Further studies are warranted in order to clarify the pathogenesis of the development of MDS/sPAP.…”
Section: Discussionsupporting
confidence: 69%
“…Aza treatment results in reduced DNA methylation as demonstrated by several studies in vivo and in vitro , although the degree of demethylation seems to be limited [4, 1115]. A plethora of in vitro studies have investigated the in vitro effects of Aza, however, only a limited number of these have used primary MDS cells in the experiments [16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to genetic alterations, epigenetic modi cations especially in DNA methylation have been shown involved in cancer progression including MDS [24][25][26]. Previous studies almost focused on the single gene change during MDS progression, such as CDKN2B, SOCS1, NR4A2, ABAT, ID4, GPX3, SOX30, and etc [9][10][11][27][28][29][30]. However, little studies showed the whole-genome DNA methylation alterations during MDS progression.…”
Section: Discussionmentioning
confidence: 99%